Associations of cardiorespiratory fitness with structural brain networks in ageing: insights from The Maastricht Study - Kristina Ukropcova; Kay Deckers; Annemarie Koster; Joost J. A. de Jong; Jacobus F. A. Jansen; Walter H. Backes; Hans H. C. M. Savelberg; Carla van der Kallen; Miranda T. Schram; Sebastian Köhler; Veerle van Gils (GeroScience, 2026)

The role of modifiable risk factors on the cerebral myelin content and cognition: findings from The Maastricht Study - Gerhard S. Drenthen; Walter H. Backes; Sebastian Köhler; Kay Deckers; Miranda T. Schram; Simone J. P. M. Eussen; Willemijn J. Jansen; Jacobus F. A. Jansen (GeroScience, 2026)
Lifestyle-related factors may affect cognition and increase the risk of developing dementia. However, the neurobiological mechanisms underlying the effect of lifestyle-related factors on the brain are not yet fully understood. Myelin, a vital element of brain health, has previously been shown to be involved in dementia-related cognitive decline. However, whether it plays a role in the relation between lifestyle-related factors and cognitive performance has not been studied. The cerebral myelin content of 4653 participants (51% female, aged 59 ± 9 years) from The Maastricht Study was estimated using the T1w/FLAIR-ratio, and lifestyle-related factors were summarized using the LIBRA-score. Multivariable linear regression models, corrected for the effects of age, sex and education, were used to investigate whether lifestyle-related factors are associated with myelin. Moreover, whether myelin can partly explain the relationship between lifestyle-related factors and cognition was explored using a mediation analysis across three cognitive domains (memory, executive functioning and processing speed). An unhealthy lifestyle (i.e. higher LIBRA score) is significantly associated to a lower cerebral myelin content ( β = −0.24, 95% CI [−0.26 −0.22], and p < 0.001). Furthermore, lower cerebral myelin content associates to worse cognitive performance ( β = 0.14, 95% CI [0.11 0.17], and p < 0.001). Moreover, myelin has a partially mediating effect of 15%, indicating that it partly explains the relation between lifestyle-related factors and cognition. These results show that myelin content might help explain the mechanisms through which lifestyle-related factors influence cognition, potentially allowing for specific and early lifestyle interventions aimed at preventing or delaying cognitive decline and dementia. Graphical abstract

The neurovascular unit and its correlation with cognitive performance in patients with cerebral small vessel disease: a canonical correlation analysis approach - Maud van Dinther; Paulien H. M. Voorter; Eleana Zhang; Sander M. J. van Kuijk; Jacobus F. A. Jansen; Robert J. van Oostenbrugge; Walter H. Backes; Julie Staals (GeroScience, 2024)
Growing evidence indicates an important role of neurovascular unit (NVU) dysfunction in the pathophysiology of cerebral small vessel disease (cSVD). Individually measurable functions of the NVU have been correlated with cognitive function, but a combined analysis is lacking. We aimed to perform a unified analysis of NVU function and its relation with cognitive performance. The relationship between NVU function in the white matter and cognitive performance (both latent variables composed of multiple measurable variables) was investigated in 73 patients with cSVD (mean age 70 ± 10 years, 41% women) using canonical correlation analysis. MRI-based NVU function measures included (1) the intravoxel incoherent motion derived perfusion volume fraction ( f) and microvascular diffusivity ( D* ), reflecting cerebral microvascular flow; (2) the IVIM derived intermediate volume fraction ( f int ), indicative of the perivascular clearance system; and (3) the dynamic contrast-enhanced MRI derived blood–brain barrier (BBB) leakage rate ( K i ) and leakage volume fraction ( V L ), reflecting BBB integrity. Cognitive performance was composed of 13 cognitive test scores. Canonical correlation analysis revealed a strong correlation between the latent variables NVU function and cognitive performance ( r 0.73; p = 0.02). For the NVU, the dominating variables were D *, f int , and K i . Cognitive performance was driven by multiple cognitive tests comprising different cognitive domains. The functionality of the NVU is correlated with cognitive performance in cSVD. Instead of focusing on individual pathophysiological mechanisms, future studies should target NVU dysfunction as a whole to acquire a coherent understanding of the complex disease mechanisms that occur in the NVU in cSVD. Trial registration: NTR3786 (Dutch Trial Register).

Extracerebral microvascular dysfunction is related to brain MRI markers of cerebral small vessel disease: The Maastricht Study - Maud van Dinther; Miranda T. Schram; Jacobus F. A. Jansen; Walter H. Backes; Alfons J. H. M. Houben; Tos T. J. M. Berendschot; Casper G. Schalkwijk; Coen D. A. Stehouwer; Robert J. van Oostenbrugge; Julie Staals (GeroScience, 2022)
Background Cerebral small vessel disease (cSVD) is a late consequence of cerebral microvascular dysfunction (MVD). MVD is hard to measure in the brain due to its limited accessibility. Extracerebral MVD (eMVD) measures can give insights in the etiology of cerebral MVD, as MVD may be a systemic process. We aim to investigate whether a compound score consisting of several eMVD measures is associated with structural cSVD MRI markers. Methods Cross-sectional data of the population-based Maastricht Study was used ( n = 1872, mean age 59 ± 8 years, 49% women). Measures of eMVD included flicker light-induced retinal arteriolar and venular dilation response (retina), albuminuria and glomerular filtration rate (kidney), heat-induced skin hyperemia (skin), and plasma biomarkers of endothelial dysfunction (sICAM-1, sVCAM-1, sE-selectin, and von Willebrand factor). These measures were standardized into z scores and summarized into a compound score. Linear and logistic regression analyses were used to investigate the associations between the compound score and white matter hyperintensity (WMH) volume, and the presence of lacunes and microbleeds, as measured by brain MRI. Results The eMVD compound score was associated with WMH volume independent of age, sex, and cardiovascular risk factors (St β 0.057 [95% CI 0.010–0.081], p value 0.01), but not with the presence of lacunes (OR 1.011 [95% CI 0.803–1.273], p value 0.92) or microbleeds (OR 1.055 [95% CI 0.896–1.242], p value 0.52). Conclusion A compound score of eMVD is associated with WMH volume. Further research is needed to expand the knowledge about the role of systemic MVD in the pathophysiology of cSVD.

Blood–brain barrier leakage at baseline and cognitive decline in cerebral small vessel disease: a 2-year follow-up study - Danielle Kerkhofs; Sau May Wong; Eleana Zhang; Renske Uiterwijk; Erik I. Hoff; Jacobus F. A. Jansen; Julie Staals; Walter H. Backes; Robert J. van Oostenbrugge (GeroScience, 2021)
Blood–brain barrier (BBB) dysfunction is one of the pathophysiological mechanisms in cerebral small vessel disease (SVD). Previously, it was shown that BBB leakage volume is larger in patients with SVD compared with controls. In this study, we investigated the link between BBB leakage and cognitive decline over 2 years in patients with cSVD. At baseline, 51 patients with clinically overt cSVD (lacunar stroke or mild vascular cognitive impairment) received a dynamic contrast-enhanced MRI scan to quantify BBB permeability in the normal-appearing white matter (NAWM), white matter hyperintensities (WMH), cortical grey matter (CGM), and deep grey matter (DGM). Cognitive function in the domain executive function, information processing speed, and memory was measured in all patients at baseline and after 2 years. The association between baseline BBB leakage and cognitive decline over 2 years was determined with multivariable linear regression analysis, corrected for age, sex, educational level, baseline WMH volume, and baseline brain volume. Regression analyses showed that higher baseline leakage volume and rate in the NAWM and CGM were significantly associated with increased overall cognitive decline. Furthermore, higher baseline leakage volume in the NAWM and CGM, and higher baseline leakage rate in the CGM were significantly associated with increased decline in executive function. This longitudinal study showed that higher BBB leakage at baseline is associated with stronger cognitive decline, specifically in executive function, over 2 years of follow-up in patients with cSVD. These results emphasize the key role of BBB disruption in the pathophysiology and clinical progression of cSVD.

Imaging the role of blood–brain barrier disruption in normal cognitive ageing - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
To investigate whether blood–brain barrier (BBB) disruption is a potential mechanism of usual age-related cognitive decline, we conducted dynamic contrast–enhanced (DCE) MRI to measure BBB leakage in a healthy sample, and investigated the association with longitudinal cognitive decline. In a sample of neurologically and cognitively healthy, older individuals, BBB leakage rate in the white and grey matter and hippocampus was measured using DCE MRI with pharmacokinetic modelling. Regression analysis was performed to investigate whether the leakage rate was associated with decline in cognitive performance (memory encoding, memory retrieval, executive functioning and processing speed) over 12 years. White and grey matter BBB leakages were significantly associated with decline in memory retrieval. No significant relations were found between hippocampal BBB leakage and cognitive performance. BBB disruption already being associated with usual cognitive ageing, supports that this neurovascular alteration is a possible explanation for the cognitive decline inherent to the ageing process. More insight into BBB leakage during the normal ageing process could improve estimation and interpretation of leakage rate in pathological conditions. The current results might also stimulate the search for strategies to maintain BBB integrity and help increase the proportion people experiencing successful ageing. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Increase in blood–brain barrier leakage in healthy, older adults - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Ed H. B. M. Gronenschild; Walter M. Palm; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
Blood–brain barrier (BBB) breakdown can disrupt nutrient supply and waste removal, which affects neuronal functioning. Currently, dynamic contrast-enhanced (DCE) MRI is the preferred in-vivo method to quantify BBB leakage. Dedicated DCE MRI studies in normal aging individuals are lacking, which could hamper value estimation and interpretation of leakage rate in pathological conditions. Therefore, we applied DCE MRI to investigate the association between BBB disruption and age in a healthy sample. Fifty-seven cognitively and neurologically healthy, middle-aged to older participants (mean age: 66 years, range: 47–91 years) underwent MRI, including DCE MRI with intravenous injection of a gadolinium-based contrast agent. Pharmacokinetic modeling was applied to contrast concentration time-curves to estimate BBB leakage rate in each voxel. Subsequently, leakage rate was calculated in the white and gray matter, and primary (basic sensory and motor functions), secondary (association areas), and tertiary (higher-order cognition) brain regions. A difference in vulnerability to deterioration was expected between these regions, with especially tertiary regions being affected by age. Higher BBB leakage rate was significantly associated with older age in the white and gray matter, and also in tertiary, but not in primary or secondary brain regions. Even in healthy individuals, BBB disruption was stronger in older persons, which suggests BBB disruption is a normal physiologically aging phenomenon. Age-related increase in BBB disruption occurred especially in brain regions most vulnerable to age-related deterioration, which may indicate that BBB disruption is an underlying mechanism of normal age-related decline. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Blood–brain barrier leakage in relation to white matter hyperintensity volume and cognition in small vessel disease and normal aging - C. Eleana Zhang; Sau May Wong; Renske Uiterwijk; Walter H. Backes; Jacobus F. A. Jansen; Cécile R. L. P. N. Jeukens; Robert J. van Oostenbrugge; Julie Staals (Brain Imaging and Behavior, 2019)

Glyoxalase-1 overexpression partially prevents diabetes-induced impaired arteriogenesis in a rat hindlimb ligation model - Olaf Brouwers; Liang Yu; Petra Niessen; Jos Slenter; Karolien Jaspers; Allard Wagenaar; Mark Post; Toshio Miyata; Walter Backes; Coen Stehouwer; Maya Huijberts; Casper Schalkwijk (Glycoconjugate Journal, 2016)